Microsatellite analysis of genetic structure in the mangrove species Avicennia marina (Forsk.) Vierh. (Avicenniaceae) - Maguire, T. L.; Saenger, P.; Baverstock, P.; Henry, R. (Molecular ecology, 2000)
The level of genetic variation throughout the entire worldwide range of the mangrove species Avicennia marina (Forsk.) Vierh. was examined using microsatellite markers. Three microsatellite loci detected high levels of allelic diversity (70 alleles in total), essential for an accurate estimation of population genetic parameters. The informativeness of the microsatellite loci tended to increase with increasing average number of repeats. The levels of heterozygosity detected for each population, over all loci, ranged from 0.0 to 0.8, with an average of 0.407, indicating that some populations had little or no genetic variation, whereas others had a large amount. Populations at the extremes of the distribution range showed reduced levels of heterozygosity, and significant levels of inbreeding. This is not unexpected as these populations may be subject to founder effects and environmental constraints. The presence of genetic structure was tested in A. marina populations using three models: (i) a single panmictic model; (ii) the discrete subpopulation model; and (iii) the isolation by distance model. The discrete subpopulations model was supported by the overall measures of population differentiation based on the infinite alleles model (F‐statistics), and the stepwise mutation model (R statistics). In addition, an analysis of molecular variance (amova), using both theoretical models, found that most of the variation was between populations (41–71%), and within individuals in the total population (31–49%). There was little variation among individuals within populations (0–10%). There was no significant isolation by distance. The high levels of genetic differentiation observed among populations of A. marina may be due to environmental and ecological factors, particularly past sea level and climatic changes.